2015
DOI: 10.7287/peerj.preprints.913v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationships of NDVI, Biomass, and Leaf Area Index (LAI) for six key plant species in Barrow, Alaska

Abstract: Here we investigate relationships between NDVI, Biomass, and Leaf Area Index (LAI) for six key plant species near Barrow, Alaska. We explore how key plant species differ in biomass, leaf area index (LAI) and how can vegetation spectral indices be used to estimate biomass and LAI for key plant species. A vegetation index (VI) or a spectral vegetation index (SVI) is a quantitative predictor of plant biomass or vegetative vigor, usually formed from combinations of several spectral bands, whose values are added, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 29 publications
(55 reference statements)
5
45
1
1
Order By: Relevance
“…The simulation could proceed based on growing degree days, or a sub-function simulation may be required, which restricts the applications of these models [4,5,11,45] to some extent. In this study, the RNDVI models based on RAGDD were constructed for both Japonica and Indica high-yield rice types.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation could proceed based on growing degree days, or a sub-function simulation may be required, which restricts the applications of these models [4,5,11,45] to some extent. In this study, the RNDVI models based on RAGDD were constructed for both Japonica and Indica high-yield rice types.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that NDVI could be a good predictor of forest carbon at low forest carbon values 15,16 . Contrary to this conclusion, Table 1 shows the result of regression from the study area in the form of coefficient of determination (R 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…When relating NDVI to vegetation parameters, including Leaf Area Index, biomass and production, saturation in the relationship can occur [36,37]. Saturation of the NDVI-ANPP relationship was observed in the summer images and is shown by the lack of relationship between NDVI and ln(ANPP) (Figure 3 July images) and the lack of spread of NDVI values in the summer ( Figure 5).…”
Section: Limitations and Future Workmentioning
confidence: 99%